THE POTENTIAL USE OF MINI WIND TURBINES AT SEKOLAH TINGGI ILMU PELAYARAN AS AN ALTERNATIVE RENEWABLE ELECTRICAL ENERGY SOURCE - Yudhiyono, Yudhiyono; MUDAKIR, MUDAKIR; ARIYANTO, ARIYANTO (Meteor STIP Marunda, 2023)
This study investigates the potential deployment of mini wind turbines at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta as an alternative renewable electrical energy source. Situated along the northern coastal zone of Marunda, Jakarta, the campus is geographically positioned in a corridor with consistent coastal wind exposure, presenting a viable opportunity for small-scale wind energy harvesting. The research adopts a qualitative descriptive approach through an exploratory case study design. Data were collected using in-depth interviews with campus leadership, engineering faculty, campus electricians, and cadets, complemented by structured field observations and secondary document analysis covering historical wind speed records from BMKG, campus electricity consumption data, and institutional master plans. Data trustworthiness was ensured through source triangulation and method triangulation. The findings were analyzed using the Miles, Huberman, and Saldana interactive model comprising data reduction, data display, and conclusion drawing/verification. The results indicate that STIP Jakarta possesses favorable site conditions including open rooftop areas and coastal wind corridors, adequate electrical grid infrastructure for on-grid or off-grid integration, and strong institutional policy alignment through its green campus commitment. However, technical challenges related to marine corrosion, structural load-bearing capacity, and personnel readiness for routine maintenance require targeted mitigation. The study concludes that mini wind turbines hold significant potential as both a supplementary renewable energy source and an educational laboratory facility for maritime cadets, provided that structured implementation planning and capacity-building measures are adopted.